PROBLEMATIKA PELAKSANAAN KURIKULUM MERDEKA DI RA AL-CHAERIYAH SILOPO KAB. POLEWALI MANDAR - Aldawiah, Aldawiah; Tadzkirah, Tadzkirah; Palintan, Tien Asmara; Natsir, Tri Ayu Lestari (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Early childhood education plays a crucial role in shaping the foundation of character and competence in students. The Merdeka Curriculum emerges as a response to the need for more flexible, contextual education that focuses on strengthening character through the Pancasila Student Profile. However, the implementation of this curriculum in various educational units, including RA Al-Chaeriyah Silopo, faces several challenges. This study aims to identify the issues that arise in the implementation of the Merdeka Curriculum and the strategies employed by teachers to address them. The research uses a descriptive qualitative approach, with data collection techniques including observation, in-depth interviews with the principal and teachers, as well as documentation. The research findings show that the implementation of the Merdeka Curriculum at RA Al-Chaeriyah Silopo faces challenges such as delayed information from the government, a lack of teacher training, limited understanding of the Merdeka Curriculum concept, and insufficient teaching materials and facilities. Nevertheless, both the teachers and the principal demonstrate high enthusiasm by participating in training, utilizing KKG forums, seeking independent references, and developing teaching materials that align with local conditions and the needs of students. These strategies demonstrate adaptive efforts made to implement the curriculum optimally. The study concludes that the success of the Merdeka Curriculum implementation is greatly influenced by the readiness of human resources, institutional support, and the creativity of teachers in responding to limitations. Therefore, continued support from the government, society, and educational institutions is necessary to ensure the effective, contextual, and sustainable implementation of the Merdeka Curriculum at the RA level. ABSTRAKPendidikan anak usia dini memegang peran penting dalam membentuk dasar karakter dan kompetensi peserta didik. Kurikulum Merdeka hadir sebagai respons terhadap kebutuhan pendidikan yang lebih fleksibel, kontekstual, dan berorientasi pada penguatan karakter melalui Profil Pelajar Pancasila. Namun, implementasi kurikulum ini di berbagai satuan pendidikan, termasuk RA Al-Chaeriyah Silopo, menghadapi berbagai tantangan. Penelitian ini bertujuan untuk mengidentifikasi problematika yang muncul dalam pelaksanaan Kurikulum Merdeka serta strategi yang dilakukan guru untuk mengatasinya. Penelitian menggunakan pendekatan kualitatif deskriptif, dengan teknik pengumpulan data melalui observasi, wawancara mendalam dengan kepala sekolah dan guru, serta dokumentasi. Hasil penelitian menunjukkan bahwa pelaksanaan Kurikulum Merdeka di RA Al-Chaeriyah Silopo Terdapat kendala seperti keterlambatan informasi dari pemerintah, kurangnya pelatihan guru, keterbatasan pemahaman terhadap konsep Kurikulum Merdeka, serta minimnya sarana dan bahan ajar. Meskipun demikian, guru dan kepala sekolah menunjukkan antusiasme tinggi dengan mengikuti pelatihan, memanfaatkan forum KKG, mencari referensi mandiri, serta menyusun perangkat ajar sesuai dengan kondisi lokal dan kebutuhan peserta didik. Strategi ini memperlihatkan upaya adaptif yang dilakukan untuk menjalankan kurikulum secara optimal. Penelitian ini menyimpulkan bahwa keberhasilan implementasi Kurikulum Merdeka sangat dipengaruhi oleh kesiapan sumber daya manusia, dukungan institusi, dan kreativitas guru dalam merespons keterbatasan. Oleh karena itu, diperlukan dukungan berkelanjutan dari pemerintah, masyarakat, dan lembaga pendidikan agar pelaksanaan Kurikulum Merdeka di tingkat RA dapat berjalan efektif, kontekstual, dan berkelanjutan.